THE SELECTION PROCESS MONITORING APPLICATION TO IMPROVE EMPLOYEE PERFORMANCE AT PT MEGA ADIYASA MANDIRI MALANG - Fullchis Nurtjahjani; Ane Fany Novitasari; Kadek Suarjuna Batubulan; Vipkas Al Hadid Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
As a company engaged in providing human resource services, PT Mega Adiyasa Mandiri needs to improve the quality of the human resources it produces to become a superior company in this field. With the selection process that has been carried out so far. Thus PT Mega Adiyasa Mandiri needs to improve the optimization of selection activities. The data collection techniques used in this study are observation and interviews. The method used for making the selection process monitoring application is the pieces method. After the application development process is complete, a system trial will be carried out using the white box method. PT Mega Adiyasa Mandiri is a provider of human resources services that are superior, insightful and competent in various fields. The use of monitoring applications for the selection process makes a positive contribution to PT Mega Adiyasa Mandiri. Companies can have integrated data between prospective workers and users. Companies can easily obtain input from users regarding the performance of the human resources that have been used. In addition, this application also makes it easy for companies to ensure that prospective workers are of good quality